Personal prerequisites for the psychological safety of Russian students in close intercultural interaction - E. V. Egamberdieva; N. A. Tsvetkova (Вестник университета)
The article is based on the data of an empirical study carried out in 2022 with the participation of 148 students of the MGIMO University – Russian’s citizens, one half of whom identified themselves as Russian, and the other attributed themselves to other ethnic groups. The personal prerequisites for psychological safety, which are characteristic of Russian students who define themselves as “Russian”, include: a normative variant of the development of five basic characteristics that make up the structure of a “normal” personality; tolerance as a personality trait; average and a lower authoritarianism index relative to the other group; components of self-actualisation – support, behavioural flexibility, cognitive needs; medium-developed subjectivity; adequate level of psychological defenses. The students – Russian citizens who attributed themselves to other ethnic groups, have: a normative version of the development of the five basic characteristics of a “normal” personality; an average overall level of tolerance and authoritarianism as well as self-actualisation; an adequately high level of belief in the fairness of the world, their good fortune and ability to control events; activity as a leading component of subjectivity; a willingness to establish a social distance with other ethnic groups that facilitates dialogue. Based on the results of the survey, personal preconditions that can cause inter-ethnic conflicts have been identified.